Memórias de professoras alfabetizadoras do MOBRAL em Fortaleza - Gomes, Luciana Kellen de Souza (2012)
The present study tries to redo the history of MOBRAL in Fortaleza at the 70's, from the memories of the teachers that worked at that time. This will also talk about the political bases and philosophies of MOBRAL, from the analytical concepts of literacy among youngsters and adults through the history of Brazil.This research was developed with bases on the memories of formal teachers of MOBRAL, showing the day by day of this experience, forgotten for a long time. Therefore, we chose the oral history as an approach for this study (interviews with formal teachers), as well as an analytical look of the official documents of MOBRAL and documents from IBGE. According to Le Goff (1990), the history of the everyday, comes from the merging of history with different areas and manifests a different perspective bases on memory. And that is exactly the record of the living memory that gives peculiarity and uniqueness. This way, history, memory and oblivioness of the education of MOBRAL in Fortaleza lives at the memories of teachers, that daily confronted themselves with adversity, anguish and victories of the process teaching- learning of youngsters and adults at this formal teaching system. The history of Mobral is recountted from the tales of people that lived the system and registered from a social-historical research where, teachers, as subjects, told the stories of their perceptions, conjectures, thoughts and memories about MOBRAL, and had garanteed their historycal views about a goverment program that had a huge impact on the path of youngsters and adults of Brazil.